Hepatitis C virus genotype 4 in Southern and Central Spain does not come from recent foreign migration waves - Di Lello, Federico Alejandro (2013)
Hepatitis C virus genotype 4 (HCV-4) is highly prevalent in Spain, but the information on the molecular characterization of HCV-4 in this region is scarce. Due to this, the molecular characteristics and the evolution of HCV-4 infection in Seville were analyzed (Southern Spain) and compared them with samples from Madrid. HCV genotype was determined by LIPA 2.0 assay and confirmed by sequence analysis of NS5B. Phylogenetic tree was estimated by MEGA 5.10. Bayesian coalescent-based methods were used to estimate the substitution rate and the age of the most recent common ancestor (MRCA). In the phylogenetic analysis of 50 NS5B HCV-4 from Seville and 11 from Madrid, 2 clusters were distinguished: The first cluster (HCV-4a) included 48% of the sequences from Seville and 9% of sequences from Madrid. The second cluster included the remaining sequences belonging to HCV-4d. The mean estimated substitution rate was 2.39 × 10−3 for HCV-4a and 1.81 × 10−3 for HCV-4d for Seville and 2.32 × 10−3 for HCV-4d from Madrid. The date for MRCA was estimated to be around 1981–1984 for HCV-4 from Seville. The dates for MRCA were dated before the recent flow of immigration in Spain. Therefore, the results presented in this study argues against the possibility of a foreign introduction of the HCV-4 from other regions with high prevalence, at least during the last two, decades in which there was a great flow of immigrants. Additionally, an unusual high prevalence of subtype 4a was observed in Seville.